Pengaruh Inovasi Produk dan Content Marketing Terhadap Minat Beli Produk Kopi Siap Minum Good Day - Irvara Wulandari, Shela; Setiyarini, Triana (CV. ULIL ALBAB CORP, 2025)
This study aims to analyze the effect of product innovation and content marketing on consumer purchasing interest in Good Day ready to drink coffee products. This study uses a quantitative approach with a survey method through an online questionnaire involving 100 respondents who are students of the Faculty of Economics and Business, Trunojoyo University, Madura. The sampling technique used purposive sampling, and the data were analyzed using the PLS-SEM method with the SmartPLS 4.0 application. The results show that product innovation and content marketing have a positive and significant effect on consumer purchasing interest. These findings indicate that product innovation oriented towards quality, modification, and market needs, as well as creative and relevant content marketing strategies on social media, can increase consumer interest in Good Day ready to drink coffee products.